The Case Study as a Method of Studying the Processes on a Field of Social Communication - Filanowski, Błażej (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter discusses the case study as a method used in research on complex and processual phenomena in the area of social communication. The author points to the methodological diversity which becomes a challenge for the researcher choosing those methods. Taking into account existing theoretical concepts in the proposed research process is one of the key decisions that he or she must make. This problem is analyzed on the examples of four research attitudes distinguished by Hans-Gerd Ridder.